2019
DOI: 10.1016/j.jtcvs.2018.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid annular plane systolic excursion is significantly reduced during uncomplicated coronary artery bypass surgery: A prospective observational study

Abstract: Objectives: Longitudinal shortening constitutes most of the right ventricle (RV) contraction in the normal heart. However, after even uncomplicated cardiac surgery with preserved RV function a significant and sustained decrease in longitudinal contraction expressed as a reduction in tricuspid annular plane systolic excursion (TAPSE) has been observed. Why and exactly when this happens remains unsettled. The aim of this study was to evaluate the magnitude and timing of changes in TAPSE in relation to sternotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
3
9
1
Order By: Relevance
“…In agreement with our study, 50 patients underwent CABG were included in a study by Korshin, et al [11], who found signi icant reduction in TAPSE after surgery [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our study, 50 patients underwent CABG were included in a study by Korshin, et al [11], who found signi icant reduction in TAPSE after surgery [11].…”
Section: Discussionsupporting
confidence: 90%
“…Also in harmony with us among ifty patients were included in the Korshin, et al, [11], study, the gender distribution revealed more male than female patients [11].…”
Section: Discussionmentioning
confidence: 51%
“…Previous reports suggested that the RV function evaluated by the tricuspid annular plane systolic excursion (TAPSE), or the systolic tricuspid annular velocity (RV S'), is impaired after cardiac surgery. [1][2][3][4] These findings have been corroborated by deformation analysis assessing the longitudinal contraction of the RV lateral free wall. 5,6 In contrast, RV ejection fraction (EF), or RV fractional area change (FAC), seems to remain stable immediately postoperatively.…”
mentioning
confidence: 55%
“…Post cardiopulmonary bypass (CPB) right ventricular (RV) dysfunction has been extensively described in cardiac surgery in past years, and attributed to either cardioplegia, myocardial hypothermia, cardiac stunning, and pericardiectomy [1][2][3]. More recently, both a different contraction pattern [4,5] and a dissociation of RV output from RV longitudinal contraction [6] have been described in this context, leading to some re-interpretation of what previously observed.…”
mentioning
confidence: 89%